The Comparison of Investment Decision Frame and Belief-adjustment Model on Investment Decision Making - Almilia, Luciana Spica; Wulanditya, Putri; Nita, Riski Aprilia (Jurnal Keuangan dan Perbankan, 2018)
Investors sometimes performed the irrational behavior in the stock market. Framing indicated that decision maker would respond with different ways on the problem of the similar decision if the problem was presented in different format. Framing effect was need to be wary because it can created bias in decision making.  We examined investment decision making based on belief-adjustment model and investment decision frame.  The research method a mixed design experiment (between and within subject). Research participants in this research were non-professional investors.  The numbers of participants in this research were 113 people.  We found that participants gave a different response when receiving non-accountancy information (expressive decision frame) with different presentation patterns that were step-by-step and end-of-sequence. The other findings of these research showed that there was no different response between participants receiving accountancy information (financial decision frame) and participants receiving non-accountancy information (expressive decision frame) in end-of-sequence presentation pattern.  However, when participants received accountancy information compared to non-accountancy information in step-by-step presentation pattern, it showed that there was a different response. The overall results of the study indicated that the investment decision frame affects the investment decision making when the information presentation pattern was step-by-step.JEL Classification: D82, G11DOI: https://doi.org/10.26905/jkdp.v22i3.1880